GAMBARAN KARAKTERISTIK KEJADIAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI RSUD KARANGAYAR - Anik Sulistiyowati (OVUM : Journal of Midwifery and Health Sciences, 2021)
Hyperemesis gravidarum is excessive nausea and vomiting that can interfere with daily activities and can even endanger life. Based on the incidence of hyperemesis gravidarum in Karanganyar Hospital, medical records of pregnant women in the first trimester who experienced hyperemesis gravidarum were obtained as many as 109 people. The purpose of this study was to describe the characteristics of the incidence of hyperemesis gravidarum in first trimester pregnant women at Karanganyar Hospital. This type of research uses a descriptive quantitative approach, non-random (non-probability) sampling method and saturated sampling technique for 86 people. Analysis of the data with univariate analysis. Data were collected with medical record data. The results showed that the characteristics of pregnant women in the first trimester who experienced hyperemesis gravidarum were the most dominant, namely characteristics based on work. The characteristics of the majority of pregnant women in the first trimester who experience hyperemesis gravidarum based on age <20 years (40.7%), based on the number of gravida namely primipara (54.7%), based on education namely basic education (54.7%), based on occupation, namely work (62.5%). The conclusion of this study is that the characteristics of first trimester pregnant women who experience hyperemesis gravidarum are in the age category < 20 years, primipara, basic education and work.